OS CURSOS SUPERIORES DE TECNOLOGIA E O MUNDO DO TRABALHO - Edson Andrade dos Reis (Universidade Federal de Santa Catarina, 2012)
With increasing technological innovation within organizations, it became clear the need for a close relationship between the institution of knowledge production, scientific and technical knowledge and business. The main objective of this work is to address the interactions of courses in technology and business, in order to assist the analysis of a course of technology and its integration into the work together as a way to contribute to the development of society and the increasing percentage of the population with higher education in the country. in this study. Data collection was performed by the method of interviews with corporate managers regions of Brasilia, Sao Paulo and Joinville using a semi-structured questionnaire. The survey was carried out between 20 July and 10 September 2012, where 51 questionnaires were collected, of which 24 questionnaires from managers of the city of Brasília, 18 questionnaires from managers of the city of Joinville and 9 questionnaires city of São Paulo. The courses in technology are not developing the potential of vocational higher education in its fullness mainly by the lack of interaction between enterprises in shaping the curriculum matrices.